Analysis of the Influence of the School Environment on Student Learning Motivation - Noveri Amal Jaya Harefa; Bonafetura Niamonio Ziliwu; Solina Zendrato; Wecan Kartika Hidayati Gea; Yunulisman Telaumbanua (Journal of Social Science Utilizing Technology, 2024)
Background. Education is the main pillar in the development of a country, where the quality of education plays a crucial role in forming the next generation of high quality and competitiveness. Student learning motivation in Junior High School is a very important factor in achieving this goal. Purpose. This research aims to investigate the influence of the school environment on students” learning motivation at State Junior High School 1 Alasa Talumuzoi. Method. The research method used is qualitative with a descriptive approach. Data was collected through questionnaires, interviews and direct observation of 20 students in class VIII-A.  Results. The results of the questionnaire data analysis show that the influence of the school environment on student learning motivation is in the medium category, with a score percentage of 49.55%. A clean, beautiful, safe and comfortable school environment makes a positive contribution in increasing students” learning motivation by creating an atmosphere that is conducive to learning. Positive interactions between students, teachers and school staff also play an important role in creating a pleasant learning climate. Conclusion. This research provides a deeper understanding of how the school environment at State Junior High School 1 Alasa Talumuzoi plays a role in shaping student learning motivation. The implication of this research is that efforts are needed to optimize the school environment in order to improve the quality of learning and overall student academic achievement.